Mediações pedagógicas no uso de aplicativos de leitura e escrita da Play Store: implicações para alfabetização e letramento de crianças com deficiência intelectual - Nunes, Camila Almada (2022)
This dissertation aims to analyze the implications of the use of educational applications of reading and writing for literacy of children with intellectual disabilities (ID). In this sense, in the specific objectives were to identify the potential of applications for literacy of children with intellectual disabilities, investigate the skills and/or competencies of reading and writing mobilized by children from mediations with the applications and to verify the involvement of children and learning linked to literacy through the use of applications. The theoretical basis is anchored in the cultural-historical theory of Vygotsky (1989, 1991, 1993) and the studies of Ferreiro and Teberosky (1984), Soares (1998, 2004), Rojo (1998, 2009, 2012), Lemos (2004), Saccol (2010), Lustosa (2011, 2017, 2021) and Frías-Guzmán (2015). The methodological approach of qualitative nature, with a research-intervention bias, consisted of two phases: at first, the identification and exploration of educational reading and writing apps available in the Play Store, and, the second, of the field, consisting of pedagogical intervention activities with six children with ID, carried out in 50-minute sessions twice a week, throughout two school semesters in 2019, in the Specialized Educational Assistance Room (AEE)/Extension Project of the College of Education (FACED) of the Federal University of Ceará (UFC). All sessions were recorded, composing an image bank, watched and analyzed, being revisited in various processes and stages of categorization of lines and scenes/episodes, in addition to confrontations and comparisons of the subjects' manifestations, in the course of the study. In the 1st phase of the study 15 reading and writing applications were mapped/identified - ABC Dinos, ABC Autism, Educational Puzzles, Writing ABC, Form Words, Form Words, Children's Stories, Lele Syllables, LiliPlay Alphabet, Light of Knowledge, Mastermind, My Storybook, The Animals, Silabando and Super ABC- that were linked to the theme of written language of children. In the 2nd phase, the stage of systematized interventional situations was implemented, totaling in the end, a quantity of 45 sessions (individualized and collective) with the character of pedagogical situations structured for exploration and mediation with all the applications raised and analyzed in structure, content and usability. The data showed that the higher the level of involvement of the subjects with the use of these applications, the greater were the manifestations of attention, concentration and persistence in the task. In addition, we also verified a remarkable improvement in oral language, in spontaneous helping behavior among peers and intense motivation in pedagogical activities. However, even though most of these applications have a self-explanatory layout with audiovisual and interactive elements that facilitate understanding and the execution of possible actions, the mediation strategies were essential for self-regulation of learning, enabling the management of one's own behavior and thoughts. It should be noted that, although the intention of the study did not involve teaching objectives, it was possible to identify remarkable data: the progression of the psychogenetic levels of writing of these children, thus, the data from this research are importante with regard to the contribution to learning to write and read for students with intellectual disabilities.